JUSTIFICATION OF SCIENTIFIC FIELDS OF SOIL MECHANICS WITH INCREASING THE SPEED OF RAILWAY ROLLING STOCK - Kostiuk, M. D.; Pshinko, O. M.; Petrenko, V. D.; Tsepak, S. V. (Science and Transport Progress, 2003)
Comparative calculations of earthen railway bed have been performed and regularities of the influence of loading onto change of strains have been determined.